2011
DOI: 10.1007/s11695-011-0433-y
|View full text |Cite
|
Sign up to set email alerts
|

Xenon Anesthesia Reduces TNFα and IL10 in Bariatric Patients

Abstract: Xenon anesthesia seems able to inhibit postoperative proinflammatory cytokine imbalance in morbidly obese patients undergoing Roux-en-Y laparoscopic gastric bypass; the reduced ΔTNFα at T1 and the reduced global exposition to TNFα in the XE group may explain the reduced ΔIL10 at T1 and T2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Finally, 13 studies that included a total of 817 patients were selected for the analysis. [ 3 10 , 13 , 15 17 , 20 ] The evaluated trials included reports that were published through December 2017. The baseline characteristics of the pooled studies are summarized in Table 1 , which includes patient age and the American Society of Anesthesiologists (ASA) status, which anesthetic drugs were administered and what type of surgery was used, and the results that are relevant to the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 13 studies that included a total of 817 patients were selected for the analysis. [ 3 10 , 13 , 15 17 , 20 ] The evaluated trials included reports that were published through December 2017. The baseline characteristics of the pooled studies are summarized in Table 1 , which includes patient age and the American Society of Anesthesiologists (ASA) status, which anesthetic drugs were administered and what type of surgery was used, and the results that are relevant to the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…During the past decade, a number of randomized controlled trials (RCTs) have been published that have compared the clinical efficacies of xenon and other volatile or intravenous anesthetics. [ 3 20 ] Although one meta-analysis [ 2 ] has summarized these individual studies, it contained some specific errors and failed to include important clinical data related to propofol.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-inflammatory ( 35 ) and antioxidative ( 36 ) properties of xenon are now well known. In the study by Portier et al ( 30 ) volatile anesthesia associated to hyper or hypoxemia did not induce significant changes in isoprostanes plasma concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, two small randomized controlled trials enrolling obese surgical patients evaluated the effects of different anesthetic approaches (Table 1 ). Abramo et al[ 120 ] investigated the effects of total intravenous anesthesia (TIVA), inhalation anesthesia (sevoflurane), or xenon anesthesia on serum levels of proinflammatory cytokines (IL-6, IL-10, TNF-α) and NO. The authors observed that xenon anesthesia was superior to the other two strategies in inhibiting postoperative serum TNF-α concentrations, but found no differences in other mediators[ 120 ].…”
Section: Immunomodulatory Effects Of Anesthetics In Obesitymentioning
confidence: 99%
“…Abramo et al[ 120 ] investigated the effects of total intravenous anesthesia (TIVA), inhalation anesthesia (sevoflurane), or xenon anesthesia on serum levels of proinflammatory cytokines (IL-6, IL-10, TNF-α) and NO. The authors observed that xenon anesthesia was superior to the other two strategies in inhibiting postoperative serum TNF-α concentrations, but found no differences in other mediators[ 120 ]. The effects of ketamine on inflammatory and immune responses after short-duration procedures were similar to those previously reported in non-obese patients[ 121 ].…”
Section: Immunomodulatory Effects Of Anesthetics In Obesitymentioning
confidence: 99%